O przydatności danych gwarowych w badaniach historycznojęzykowych z zakresu leksyki (na przykładzie gwar Pogórza) - Karaś, Halina (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2024)
The article discusses the usefulness of dialect data in historical-linguistic lexical research. The dataset comprises of selected dialectisms (including knysić / knysać, kurdawy, (s)kurdawieć, kurdoc, kurdupel, despet and derivative formations) from the dialects of the Biecz area in the Subcarpathian region, i.e., dialects from the south of Lesser Poland. The dialect data is often used in etymology in order to reconstruct the formal and semantic changes that various words have undergone. It can also help set up a proper etymological hypothesis and interpret words that appear to be isolated in Polish, cf. kurdupel. The analysis of dialect data can also be useful in studying the history of words of foreign origin, their persistence in the Polish language, semantic changes and word-forming potency, cf. for example, despet and derivative formations. It is important that dialect data cited in linguistic historical research be as complete as possible, truly reflecting the state of dialect lexis, the semantics of the cited dialectisms, chronology, their formal differentiation and territorial extents. This is because selective, poor information can, at times, distort the true picture of the origin and development of the forms under discussion (cf. the example of knysać // knysić).